Soleus muscle and Achilles tendon compressive stiffness is related to knee and ankle positioning - Cruz-Montecinos, C.; Besomi, M.; Acevedo-Valenzuela, N.; Cares-Marambio, K.; Bustamante, A.; Guzmán-González, B.; Tapia-Malebrán, C.; Sanzana-Cuche, R.; Calatayud, J.; Méndez-Rebolledo, G. (Journal of Electromyography and Kinesiology, 2022)
Changes in fascicle length and tension of the soleus (SOL) muscle have been observed in humans using B-mode ultrasound to examine the knee from different angles. An alternative technique of assessing muscle and tendon stiffness is myometry, which is non-invasive, accessible, and easy to use. This study aimed to estimate the compressive stiffness of the distal SOL and Achilles tendon (AT) using myometry in various knee and ankle joint positions. Twenty-six healthy young males were recruited. The Myoton-PRO device was used to measure the compressive stiffness of the distal SOL and AT in the dominant leg. The knee was measured in two positions (90° of flexion and 0° of flexion) and the ankle joint in three positions (10° of dorsiflexion, neutral position, and 30° of plantar flexion) in random order. A three-way repeated-measures ANOVA test was performed. Significant interactions were found for structure × ankle position, structure × knee position, and structure × ankle position × knee position (p < 0.05). The AT and SOL showed significant increases in compressive stiffness with knee extension over knee flexion for all tested ankle positions (p < 0.05). Changes in stiffness relating to knee positioning were larger in the SOL than in the AT (p < 0.05). These results indicate that knee extension increases the compressive stiffness of the distal SOL and AT under various ankle joint positions, with a greater degree of change observed for the SOL. This study highlights the relevance of knee position in passive stiffness of the SOL and AT.